(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present research paper, I would like to present a critical study of Mrs. Alving’s tragic failure in her domestic life in spite of her hard work to protect her husband as well as son from the sinful life and destruction in Ghost by Henrik Ibsen. It highlights why Mrs. Alving gets failed in dissuading her husband and son from indulging in the immoral life. The struggles of her life is divided into two phases including saving and protecting her husband from indulging in immoral life and protection of her son from inheriting the bad habits from his father. I would also like to show how the social circumstances affect Mrs. Alving’s life from the very beginning of the novel to the end.